Financial Statement Analysis as a Basis for Strategic Decision Making in MSMEs: A Case Study of Liquidity, Profitability, and Cash Flow Management - Jusuf Nurdin; Nuniek Dewi Pramanik (Journal of Creative Power and Ambition (JCPA), 2025)
Financial reports play a crucial role in supporting strategic decision-making for micro, small, and medium enterprises (MSMEs). However, in practice, many MSMEs have not maximized the use of financial reports as a foundation for business evaluation and management decision-making. This article aims to examine the function of financial reports in business decision-making through a descriptive-analytical method, using a case study of an MSME in the culinary sector. The analysis focuses on the elements of financial reports, liquidity ratios, solvency, profitability, and cash flow, along with their implications for business strategy. Key findings reveal that high profits do not always reflect a healthy business if they are not accompanied by consistent operational cash flow. The case study of the MSME "Kopi Nusantara" shows that the root cause of the problem is not low sales or profitability, but rather weak working capital management, particularly inventory control and delays in cash receipts from digital channels. This article emphasizes that financial reports should be used as a managerial instrument, not merely an administrative tool. Practical implications of this research include strengthening MSME financial literacy, implementing simple, standards-based record-keeping, and utilizing financial report analysis to inform operational and strategic decisions.